Grafting methods and use of fasteners in monoembryonic, polyembryonic, and multi-stemmed jaboticaba (Plinia jaboticaba (Vell) Berg) seedlings - Baptista, Julcinara Oliveira; Lopes, José Carlos; Schmildt, Edilson Romais; de Araujo, Caroline Palacio; Alexandre, Rodrigo Sobreira (Comunicata Scientiae, 2020)
Jaboticaba is a native fruit from Brazil, appreciated for its sweet taste and organoleptic characteristics. The propagation of this fruit species occurs exclusively through seeds, which present high germination rates, although with a long period of juvenility, a fact that favors advances in studies aiming at an early fruiting. This research aimed to study a more adequate and rapid grafting method for the jaboticaba cv. Sabará. The experimental design was in randomized blocks, with 12 treatments consisting of combinations using three types of seedlings (monoembryonic, polyembryonic, and multi-stemmed), two grafting methods (top cleft and splice grafting), and two fasteners (parafilm® tape and circular clip), with three replications consisting of 10 seedlings each. The analyzed characteristics were: monoembryony (%); polyembryony (%), multi-stemming (%), grafting success rate (%), survival (%), scion length (cm), scion diameter (mm), and rootstock diameter (mm). The percentage of monoembryony (46.4%) was higher than the success rates of polyembryony (36%), and multi-stemming (17.6%). The top cleft grafting method of monoembryonic seedlings fastened with parafilm® and circular clip, and polyembryonic seedlings fastened with circular clip were the more suitable for grafting in the jaboticaba cv. Sabará.